The Implementation of Tumblr.Com in Teaching Writing - Eka Puspita Sari (STKIP PGRI Lubuklinggau, 2021)
COVID-19 pandemic in 2020 digitizes human activities. The educational field is one of the aspects that affected. The classroom activities that usually do with the teacher and students together in one room moves to the virtual class in which the teacher and the students are apart. The teachers are charged to be more creative to make an interactive class. There are various applications, educational purpose and non-educational purpose, that can be used in teaching and learning activities. Thus, this study aimed to know the students' perception of the use of learning online applications and the perception of Tumblr.com as social media to teach writing, specifically in teaching hortatory exposition text. This study uses a qualitative research design and an online survey that engaged 15 students of the English Education Department in the 4th Semester at Sarjanawiyata Tamansiswa. The result of this study displayed students' improvement in writing and a positive attitude towards the use of Tumblr in the teaching and learning process. It leads to the conclusion that Tumblr can be used as an alternative solution to having interesting activities in online the teaching and learning process.